The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1748-5967.12061
|View full text |Cite
|
Sign up to set email alerts
|

TR4 and PPARγ activities are differentially modulated by pyriproxyfen

Abstract: The TR4 orphan receptor (TR4) has been suggested to mediate the effect of pyriproxyfen (PYR), a juvenile hormone (JH) analog, on lipid metabolism in adipocytes. PYR was shown to stimulate activity of TR4 only at a relatively low concentration. Thus, the effect of PYR on the adipocyte biology at higher dosages remains unclear. Here, we demonstrate that high concentration (400 μM) of PYR is still able to promote adipogenesis of 3T3‐L1 cells. Furthermore, peroxisome proliferator‐activated receptor gamma (PPARγ) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Previously, we found that pyriproxyfen increased the activity of not only PPARγ but TR4 as well, at different concentrations (Choi et al . ). However, fenoxycarb did not significantly affect TR4 transcriptional activity, suggesting that fenoxycarb may facilitate lipid accumulation in adipocytes by specifically modulating PPARγ activity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we found that pyriproxyfen increased the activity of not only PPARγ but TR4 as well, at different concentrations (Choi et al . ). However, fenoxycarb did not significantly affect TR4 transcriptional activity, suggesting that fenoxycarb may facilitate lipid accumulation in adipocytes by specifically modulating PPARγ activity.…”
Section: Resultsmentioning
confidence: 97%
“…; Choi et al . ). Interestingly, these receptors play important roles in lipid and glucose metabolism.…”
Section: Introductionmentioning
confidence: 97%
“…We recently showed that PYR, a JH analog, can stimulate TR4 activity (Choi et al ). Thus, we tested whether PYR can inhibit the negative effect of TNFα on TR4 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids pcDNA3‐TR4, pcDNA3‐p65, pCMX‐c‐Rel, pSG‐p50, pSG5‐PPARγ, pCMX‐RXRα, pGEX3, pGEX3‐TR4‐Full, pGEX3‐TR4‐N, pGEX3‐TR4‐ΔC, pGEX3‐TR4‐LBD, pGL3‐cDR1‐Luc, pGL3‐FATP1‐DR1‐Luc, pGL3‐PPRE‐Luc and pGL3‐NFRE‐Luc were described previously (Shyr et al ; Choi et al ; Choi et al ). TNFα and rosiglitazone were purchased from Sigma Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation